Neurohormonal, hemodynamic, and electrocardiographic evaluations of healthy dogs receiving long-term administration of doxorubicin - Alves de Souza, Rute Chamié [UNESP]; Camacho, Aparecido Antonio [UNESP] (American Veterinary Medical Association (AVMA), 2006)
Objective - To evaluate diagnostic testing that could be used to establish an early diagnosis of cardiotoxicosis induced by long-term administration of doxorubicin. Animals - 13 adult mixed-breed dogs. Procedures - 7 dogs were administered doxorubicin chloride (30 mg/m2, IV, q 21 d for 168 days [cumulative dose, 240 mg/m2]), and 6 dogs received saline (0.9% NaCl) solution (5 mL, IV, q 21 d for 168 days; control group). Echocardiography, ECG, arterial blood pressure, plasma renin activity (PRA), and plasma concentrations of norepinephrine and brain natriuretic peptide (BNP) were assessed before each subsequent administration of doxorubicin and saline solution. Results - Dogs that received doxorubicin had a significant decrease in R-wave amplitude, compared with values for the control group, from 30 to 210 mg/m2. Doxorubicin-treated dogs had decreases in fractional shortening and left ventricular ejection fraction evident as early as 30 mg/m2, but significant differences between groups were not detected until 90 mg/m2 was reached. There was also a significant increase in PRA (≥ 120 mg/m2) and left ventricular end-systolic and end-diastolic dimensions (≥ 60 and ≥ 180 mg/m2, respectively). Systemic arterial pressure, remaining echocardiographic variables, and concentrations of norepinephrine and BNP had significant variations, but of no clinical importance, during doxorubicin administration. Conclusions and clinical relevance - Doxorubicin-induced cardiotoxicosis developed at 120 mg/m2, but there were no clinical signs of dilated cardiomyopathy or congestive heart failure. Echocardiography and determination of PRA were able to detect early cardiac alterations during the development of dilated cardiomyopathy, despite apparently differing degrees of sensitivity to development of doxorubicin-induced cardiotoxicosis.
Keywords: brain natriuretic peptide; doxorubicin; neurohormone; noradrenalin; sodium chloride; animal experiment; animal model; arterial pressure; cardiotoxicity; clinical feature; congestive cardiomyopathy; congestive heart failure; controlled study; diagnostic test; dog disease; drug dose regimen; early diagnosis; echocardiography; electrocardiography; female; heart hemodynamics; heart left ventricle ejection fraction; heart ventricle enddiastolic pressure; longitudinal study; male; nonhuman; noradrenalin blood level; plasma renin activity; R wave; sensitivity analysis; statistical significance; systolic blood pressure; Animals; Antibiotics, Antineoplastic; Blood Pressure; Dogs; Doxorubicin; Drug Administration Schedule; Echocardiography; Electroencephalography; Health; Heart; Neurotransmitter Agents; Animalia; Canis familiaris